Learning and institutional support for youth in higher education institutions during the COVID-19 pandemic in South Africa - Dukhi, Natisha; Sewpaul, Ronel; Zungu, Nompumelelo P.; Mokhele, Tholang; Sifunda, Sibusiso (Frontiers in Education, 2024)
Introduction: As higher education institutions (HEIs) moved from in-person to online learning during the COVID-19 pandemic, various challenges were presented. Using a large online survey conducted during the pandemic, this paper investigates the impact of COVID-19 on learning and institutional support offered to students in HEIs in South Africa.The study utilized a closed-ended questionnaire on a data-free online platform. The study sample included South African youth aged 18-35 years who were enrolled for some type of educational training or in higher education institutions (including private colleges). Data was benchmarked to the 2019 estimates of the youth population in educational institutions. Descriptive statistics are presented.Results: Among the 7011 student participants, the main challenges experienced during lockdown were loss of study time (57.9%), insufficient money for essential personal items for studying (55.8%), loss of social contact (42.2%) and insufficient money for food (40.1%). Overall, 47.0% of students reported having free access to the internet, 49.5% used personal internet or paid for internet access and 3.5% indicated having no access to internet. The majority rated their institution's eLearning portal as good or excellent, and 23.4% thought their eLearning portal was of poor quality. Significantly fewer (38.1%) technical and vocational education and training (TVET) college students indicated that their institution provided the capacity to conduct virtual learning compared to those enrolled at other types of institutions. Almost two thirds of students (66.2%) from TVET colleges experienced difficulty in communicating with their institutions. Half of the students (49.9%) reported that they had a suitable place to study during lockdown, while 78.6% had regular access to electricity during lockdown. Significantly more TVET and University of Technology students received transport to return home and fee refunds.While it was encouraging that most HEIs had capacity for online learning and made provision of internet access for students, it was concerning that students who are enrolled at TVET colleges faced more learning challenges during the lockdown. This highlights the inequality in learning support at different types of institutions, and that effective support from HEIs to students during the COVID-19 pandemic was not fully implemented.